Identification of alemtuzumab-suitable multiple sclerosis patients in Slovakia and sequencing of post-alemtuzumab immunomodulatory treatment - Kantorová, Ema; Vítková, Marianna; Martiníková, Martina; Cimprichová, Andrea; Fedicˇová, Miriam; Kovácˇová, Slavomíra; Mako, Miroslav; Cisár, Juraj; Hancˇinová, Viera; Szilasiová, Jarmila; Koleda, Peter; RoháIˇová, Jana; et al. (Therapeutic advances in neurological disorders, 2024)
BACKGROUND: Alemtuzumab (ALEM) is a humanised monoclonal antibody that depletes circulating lymphocytes by selectively targeting CD52, which is expressed in high levels on T- and B-lymphocytes. This depletion is followed by lymphocyte repopulation and a cytokine expression shift towards a lesser inflammatory profile, both of which may contribute to prolonged efficacy. National recommendations for enrolling and treating multiple sclerosis (MS) patients with ALEM have been established. However, there are no recommendations in place for the treatment of MS reactivation after the ALEM treatment. OBJECTIVES: To evaluate the effectiveness and safety of the use of ALEM and to analyse subsequent disease-modifying treatments (DMTs). A multidimensional prediction model was developed to make a patient-specific prognosis regarding the response to ALEM. DESIGN: A multicentre, prospective, non-controlled, non-interventional, observational cohort study. METHODS: Relapsing multiple sclerosis patients (RMSp) who received ⩾1 dose of ALEM were enrolled. In each treatment year, the following baseline and prospective data were collected: age, MS history, number, type and duration of previous disease-modifying treatment (PDMT), relapse rate (REL), expanded disability status scale (EDSS), magnetic resonance imaging and serious adverse events (AE). In cases of reactivation of MS, all data about the subsequent DMT were collected. RESULTS: A total of 142 RMSp from 10 MS Slovak Centres fulfilled the inclusion criteria. The average age was 35 years (standard error 8.56). The overall average EDSS was 3.87 (1.46) when ALEM was started. The average duration of PDMT was 6.0 (4.04) years, and the median number of PDMTs was 3 (0-5), while the patients were mostly treated with 2 or 3 DMTs (>65.00%). Post-ALEM treatment was needed in 39 cases (27.46%). The most frequent post-ALEM treatment indicated was ocrelizumab, followed by natalizumab (NAT), siponimod and cladribine. The ocrelizumab and NAT treatment bring little benefit to patients. Siponimod showed less EDSS increase in contrast to ocrelizumab and NAT. Another repopulation therapy, cladribine, may also be an effective option. Statistically significant predictors for the expected EDSS are age (p-value <0.0001), number of ALEM cycles (0.0066), high number of PDMT (0.0459) and the occurrence of relapses (<0.0001). There was no statistically significant effect on the patient's gender (0.6038), duration of disease-modifying treatment before alemtuzumab (0.4466), or the occurrence of AE (0.6668). CONCLUSION: The study confirms the positive effect of ALEM on clinical and radiological outcomes. We need more data from long-term sequencing studies.